Darwinian selection for the fittest, oldest or youngest: relative age effects in European gymnastics - Isin, A.; Bilgiç, M.; Brustio, P. R. (Sport Sciences for Health, 2025)
Purpose This study investigated relative age effects (RAEs) among artistic gymnasts participating in the last three European Championships.